Commented Dental Ethics Code (Law 35 of 1989) (2019)
The Code of Dental Ethics is a unique and pioneering work that harmonizes each of the articles contained in Law 35 of 1989 with very didactic comments made by renowned jurists, magistrates and academics of great experience with extensive national and international experience in the area of dentistry and in the ethical disciplinary legal field of the Courts of Ethical Dentistry of the country. This will be a book of obligatory reference in the education of the new generations of dentists that require a solid formation in values and ethical principles, from the perspective of the different knowledge that a dentist must have, related to the professional exercise, the relations with the patients, relationships with colleagues, clinical history, informed consent, the state, auxiliary and laboratory personnel, institutions, control bodies and the disciplinary regime for dentists, among other topics dealt with in the work. In the same way, your help as a consultation and support document for the ethical-disciplinary processes of the magistrates of the sectional courts of dental ethics and for the National Court of Dental Ethics will be very valuable. The students, Dentists, Courts of Ethics of Dentistry of Colombia and, in general, the dentistry of the country, have a work that contextualizes in a pedagogical way the ethical task of the Colombian dentist from the vision of real experiences constituting in a fundamental support for the ethical exercise of the profession, which must be framed within the highest ethical and moral principles and precepts.